Enhancing the bioactivity of Lupeol, isolated from Aloe vera leaf via targeted semi - synthetic modifications of the olefinic bond. (2019) - Gangadharan, C.; Arthanareeswari, M.; Pandiyan, R.; Ilango, K.; MohanKumar, R.
Abstract: Lupeol, a triterpenoid of biological significance is present in the aloe vera leaf. Aloe vera extracts are frequently used in the field of ayurvedic medicine and cosmetics. It contains 75 potentially active constituents: vitamins, enzymes, minerals, sugars, lignin, saponins, salicylic acids and amino acids. Lupeol is one of the active phytoconstituents with known anesthetic and anti-microbial properties. Literature indicates that modified products of this compound showed a marked increase in the bioactivity compared to parent compound. The present study involves semi-synthetic modification of Lupeol which was isolated from the aloe vera leaf extract using conventional column chromatography techniques. It is to be expected that introducing nitrogen group to the olefinic bond at C-20 will enhance the bioactivity of Lupeol. The modified compound was characterized by spectroscopic techniques like Mass and IR.